Students’ reading interest in biology learning model based on remap CIRC, GI and TGT - Nur Hayati; Siti Zubaidah; Susriyati Mahanal (Biosfer: Jurnal Pendidikan Biologi, 2020)
This study aims to determine the differences in students' reading interest in biology learning models based on remap CIRC, GI, and TGT. It is a quasi-experiment implemented in Public High School N of Malang, Indonesia and Public High School S of Malang, Indonesia in the odd semester of 2014/2015. The research population was all students of 10th grade of Public High School of Malang, Indonesia. The sampling technique was random sampling. The research sample consisted of 10th-grade science 1 of Public High School N of Malang, Indonesia, 10th-grade science 2 of Public High School N of Malang Indonesia, and 10th-grade science 1 of Public High School S of Malang, Indonesia as an experiment group; and 10th-grade science 3 of Public High School N of Malang, Indonesia as a control group. The analysis was carried out in a quantitative. The result showed that the CIRC remapping learning model had the greatest influence on students' reading interest compared to GI and TGT. The students’ reading interest scores using remap CIRC, GI, and TGT models were 82.90, 76.23, and 80.49. Remap CIRC, GI, and TGT model should be applied in biology learning because it can empower students' reading interest.